International labour law - Servais, Jean-Michel (The Hague, 2005)
"No one will deny that labour standards comprise a necessaryframework for balanced economic and social development. Yet on a global level such balanced development has not occurred, despite the existence of a rigorous body of international labour law that has been active and growing for eighty years. The implementation of this law devolves upon states; yet many states have failed to honor it. If we are to take serious steps toward a remedy for this situation, there is no better place to start than a thorough, well-researched survey and analysis of existing international labour law its sources, its content, its historical development, and an informed consideration of the barriers to its full effectiveness. This book is exactly such a resource. It provides in-depth interpretation of the crucial International Labour Organisation (ILO) instruments - Constitution, conventions, declarations, resolutions, and recommendations - as well as such other sources of law as the OECD Guidelines for Multinational Enterprises and various model and actual corporate codes of conduct."